Implementation of Appropriate Technology Used to Continuous Monitoring of Weather Conditions and Air Quality on Gili Iyang Island, Sumenep - Prisma Megantoro; Nayu Nurrohma Hidayah; Muhammad Rafi Nabil Arsalan; Arya Dwi Kustiawan; Antik Widi Anugrah; Heru Dwi Cahyono; Rizki Putra Prastio; Tahta Amrillah; Mohammad Ghani; Retna Apsari (Peneliti Teknologi Teknik Indonesia, 2023)
This article discusses community service activities that have been carried out on Gili Iyang Island, Sumenep, Madura. This activity is the application of appropriate technology, in the form of weather and air quality monitoring devices. This device is installed in two locations, namely the east side of the island and the west side of the island. The data generated from these devices can be accessed with Android smartphones by the local community and researchers. With the application of this tool, it is hoped that it can improve and advance the environmental, tourism and renewable energy sectors. In addition, this community service activity also targets training and dissemination of applied technology. Of course, the training and outreach involved the local community, which consisted of tourism awareness groups and youth organizations from the two villages on Gili Iyang Island.